Reducing intraoperative hemorrhage in type II caesarean scar pregnancy: a study protocol comparing high-intensity focused ultrasound (HIFU) pretreatment vs. hysteroscopy-guided suction curettage—an open-label, 1:1 parallel-group, superiority-design investigator-initiated trial (IIT) - Changmei Sang; Qiuling Shi; Lei Zhao; Yanjun Kang; Shuping Zhao; Zhibiao Wang (Trials)
Abstract Background The incidence of caesarean scar pregnancy (CSP) has significantly increased due to the increasing prevalence of caesarean deliveries and advances in diagnostic imaging. However, no consensus has yet been reached on the optimal therapeutic approach. Type II CSP leads to disease heterogeneity, characterized by multiple treatment options and the absence of a unified therapeutic approach. Hysteroscopic treatment for CSP has demonstrated a notable success rate, particularly in cases of type I CSP. High-intensity focused ultrasound (HIFU) ablation has emerged as a novel, non-invasive treatment option that minimizes intraoperative blood loss. However, its use may be excessive in low-risk cases. Here, we report a protocol for a randomized clinical trial designed to evaluate the necessity of performing HIFU in CSP treatment when combined with suction curettage under hysteroscopic guidance. Methods We aim to propose a randomized clinical trial that will enroll 140 participants. All participants will undergo surgical suction curettage guided by hysteroscopy, randomized into groups with or without HIFU pretreatment. Data on demographic characteristics, disease characteristics, ultrasound findings, and laboratory test results will be collected before the intervention. The primary outcome will be the intraoperative blood loss. Secondary outcomes will include the incidence of near haemorrhage, therapeutic success rates, and subsequent pregnancy outcomes within a 2-year follow-up period. Discussion Hysteroscopy has exhibited favourable therapeutic outcomes in the management of CSP, though it remains associated with a risk of intraoperative haemorrhage. HIFU has shown promise as a preoperative adjuvant modality. However, the comparative clinical advantages of standalone hysteroscopic intervention versus HIFU-assisted protocols are insufficiently explored in prospective clinical studies. This investigation seeks to assess both the standalone efficacy of hysteroscopic resection and the efficacy of combined therapy incorporating HIFU pretreatment for type II CSP. Trial registration Registration number: ChiCTR2000034332. Registration date: 2nd July 2020.